Growth kinetics of Bacillus cytotoxicus in liquid egg yolk during treatment with phospholipase A2 – A one-step global dynamic analysis - Huang, Lihan; Ahmad, Nurul Hawa; Juneja, Vijay; Stapp-Kamotani, Erika; Gabiola, Jose; Minocha, Udit; Phillips, Robert; Hooker, Marie; Walls, Isabel; Cook, Kim; Lindsay, James (Elsevier, 2024)
During commercial production of liquid egg yolk (LEY), phospholipase A2 (PLA2) is used to improve its emulsification capacity and thermal stability. The enzymatic treatment may occur at elevated temperatures such as 50 °C, potentially allowing foodborne pathogens, such as Bacillus cereus, to grow. Little knowledge is available concerning growth of B. cereus in LEY during PLA2 treatment. Therefore, the objective of this study was to investigate the growth kinetics of B. cereus during PLA2 treatment using pathogenic B. cytotoxicus NVH391-98, the most thermotolerant member in the B. cereus group, as a surrogate. Inoculated LEY samples were placed in precision programmable incubators to observe the growth of B. cytotoxicus NVH391-98 under multiple isothermal and dynamic temperature conditions between 20 and 53 °C. The bacterial growth was described using the differential Baranyi model coupled with two different secondary models. The kinetic parameters were determined using one-step dynamic inverse analysis of multiple growth curves. The least square method was used in combination with the 4th order Runge-Kutta method to solve the differential Baranyi model using multiple growth curves to determine the cardinal kinetic parameters. The results showed that B. cytotoxicus NVH391-98 can grow prolifically at 50 °C. The estimated minimum, optimum and maximum temperatures were 16.7 or 18.5, 47.8 or 48.1, and 52.1 or 52.4 °C, respectively, depending on the secondary models, with an optimum growth rate of 2.1 log colony-forming-unit (CFU)/g per hour. The dynamic model is validated using isothermal curves with reasonable accuracy. B. cytotoxicus died off slowly at 15 °C. At 55 °C, thermal inactivation was observed, with a D value of approximately 2.7 h. Holding at 55 °C or below 15 °C can effectively prevent the growth of B. cytotoxicus in egg yolk.